Motivated Strategies for Learning Questionnaire (MSLQ) : an empirical analysis of the value and expectancy theory / Wee Shu Hui, Maz Ainy Abdul Azis and Zarinah Abdul Rasit - Wee, Shu Hui; Abdul Azis, Maz Ainy; Abdul Rasit, Zarinah (Institute of Research, Development and Commercialization (IRDC), 2006)
One of the purposes of this study is to find the motivated behaviour of Accounting students towards their studies. This study was conducted on UiTM students studying accounting either as a course or as part of another course in Shah Alam. Self-efficacy, the expectancy component of motivation, refers to the confidence of the students 'own capabilities in performing a task. In contrast, the value component, task value relates to the reasons for doing the task. The results indicate that self- regulated learning is inspired by selfefficacy and task value. Students need the skill and knowledge and the will to use them to become self-regulated learners.